Perancangan Sistem Informasi Keluar – Masuk Berkas Rekam Medis Di Klinik Yakespen Utama Berbasis Visual Basic - Nadia Ramalenia (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Abstract The medical record information system is a system that functions to manage patient data, which contains the patient's identity, examination results or patient history and other supports. Medical record files that have been used or that have been released will be taken by the medical record officer for reprocessing of patient data that comes out as a result of patient visit data. The patient's medical record file system at registration at the main Medika Yakespen clinic still uses manuals and still uses paper or written sheets. So that a lot of time is wasted and the accumulation of unused files. Therefore, the system at the main Yakespen medical clinic has become less conducive due to the slowdown in the process. Therefore, by designing Visual Basic as a tool in the data processing process, so that it can facilitate the processing of medical record data or make reports in an easier and more efficient way so that it can save a lot of time and a lot of space.